VOLATILE CONSTITUENTS OF ESSENTIAL OIL OF Peumus boldus (Boldo) FROM PERU - Palomino Infante, Alfredo (2007)
Volatile compounds of peruvian Peumus boldus (Boldo) were obtained by hydrodistillation and then characterized by using GC-MS at the analytical laboratories of the Faculty of Chemistry and Chemícal Engineeríng of the University of Mayor de San Marcos. Results show the existence of 21 compounds. From them, the major component is 4-metil-7-etil-3.8-dioxatricicle [5,1 ,0 (7-4)] octane which amounts 48%, followed by 1,3,6-octatriene which is 20.9%, then 1,5 cineol with 14.9%, trans pinocarbeol with 1.5%, 4-terpineol and terpineol with 1.6% each one. The rest of compounds are in concentrations below 1 %.